Enhancing gamification in computer programming fundamental course for higher intrinsic motivation among college community students - Noraini, Mohd Banua (2024)
Gamification is increasingly being recognized as an innovative educational approach aimed at involving students more actively in their learning journey. It holds the potential to enhance the learning environment by making it more enjoyable and captivating, thereby benefiting education. This research exploring to enhancing student intrinsic motivation in Computer Programming Fundamental course through gamification. The problem statement addresses the challenge of maintaining student motivation and interest in technical subjects like programming. The objectives of the study include identifying effective gamification elements, the usability of the gamification, and evaluating their impact on student intrinsic motivation. The methodology employed in this research consists of a comprehensive three-phases: Analysis, Design and Integrate, and Evaluation. The Analysis phase involved a thorough literature review to identify suitable game elements for gamification, supporting the research objectives. Subsequently, the Design and Integrate phase focused on incorporating these game elements into gamification tools through usability and pilot tests. Finally, the Evaluation phase implemented the gamification strategies and assessed their impact on student motivation through questionnaires. The study employs a quantitative methodology, utilizing surveys to measure various constructs of motivation: attention, confidence, relevance, and satisfaction. Results show high levels of motivation across all constructs, with mean scores translating to percentages of 85.6% for attention, 86.2% for confidence, 86.8% for relevance, and 86.8% for satisfaction. The results of the study highlight the positive influence of gamification on student intrinsic motivation in Computer Programming Fundamental course. By integrating game elements effectively, students showed increased attention, relevance, confidence, and satisfaction in their learning experience. This research contributes to theoretical advancements in educational gamification, innovative applications in teaching programming, and the promotion of self-directed learning. Despite limitations such as sample size and time constraints, the study provides valuable insights into the potential of gamification to enhance student motivation in technical subjects.